Examining the relationship between structural factors, individual characteristics, and homelessness - Tseng, Y.; Scutella, R.; Wood, G.; Johnson, G.; Wood, G; Tseng, Y; Scutella, R (Australian Housing and Urban Research Institute, 2015)
This Positioning Paper is the first part of a project that seeks to examine interactions between macro structures such as changes to housing and labour markets, and the micro processes that render individuals vulnerable to homelessness. This report documents the reviews of literature, the conceptual framework and descriptive data analysis. The empirical findings will be presented in the Final Report.
AHURI Positioning Paper No. 161
AHURI Positioning Papers
Keywords: Homelessness; Housing,Affordability; Employment -- Labour Markets; Housing, communities and neighbourhoods; Labour market; Employment; Homelessness; Housing,Affordability; Labour Markets; Housing, communities and neighbourhoods; Employment and unemployment